A Compartmentalized Neuronal Cell-Culture Platform Compatible With Cryo-Fixation by High-Pressure Freezing for Ultrastructural Imaging - Tran, Hung Tri; Lucas, Miriam S.; Ishikawa, Takashi; Shahmoradian, Sarah H.; Padeste, Celestino (Frontiers in Neuroscience, 2021)
The human brain contains a wide array of billions of neurons and interconnections, which are often simplified for analysis in vitro using compartmentalized microfluidic devices for neuronal cell culturing, to better understand neuronal development and disease. However, such devices are traditionally incompatible for high-pressure freezing and high-resolution nanoscale imaging and analysis of their sub-cellular processes by methods including electron microscopy. Here we develop a novel compartmentalized neuronal co-culture platform allowing reconstruction of neuronal networks with high variable spatial control, which is uniquely compatible for high-pressure freezing. This cryo-fixation method is well-established to enable high-fidelity preservation of the reconstructed neuronal networks and their sub-cellular processes in a near-native vitreous state without requiring chemical fixatives. To direct the outgrowth of neurites originating from two distinct groups of neurons growing in the two different compartments, polymer microstructures akin to microchannels are fabricated atop of sapphire discs. Two populations of neurons expressing either EGFP or mCherry were grown in either compartment, facilitating the analysis of the specific interactions between the two separate groups of cells. Neuronally differentiated PC12 cells, murine hippocampal and striatal neurons were successfully used in this context. The design of this device permits direct observation of entire neuritic processes within microchannels by optical microscopy with high spatial and temporal resolution, prior to processing for high-pressure freezing and electron microscopy. Following freeze substitution, we demonstrate that it is possible to process the neuronal networks for ultrastructural imaging by electron microscopy. Several key features of the embedded neuronal networks, including mitochondria, synaptic vesicles, axonal terminals, microtubules, with well-preserved ultrastructures were observed at high resolution using Focused Ion Beam – Scanning Electron Microscopy (FIB-SEM) and serial sectioning - Transmission Electron Microscopy (TEM). These results demonstrate the compatibility of the platform with optical microscopy, high-pressure freezing and electron microscopy. The platform can be extended to neuronal models of brain disease or development in future studies, enabling the investigation of subcellular processes at the nanoscale within two distinct groups of neurons in a functional neuronal pathway, as well as pharmacological testing and drug screening.